PV모듈의 바이패스 다이오드 단락 고장 시 태양광어레이 회로 특성분석 - 이충근(Lee Chung-Geun); 신우균(Shin Woo-Gyun); 임종록(Lim Jong Rok); 황혜미(Hwang Hye-Mi); 주영철(Ju Young-Chul); 정영석(Jung Young-Seok); 강기환(Kang Gi-Hwan); 장효식(Chang Hyo-Sik); 고석환(Ko Suk-Whan) (한국태양에너지학회 논문집, 2019)
As the installation of photovoltaic systems increases, fire accidents of PV system grow every year. Most of PV system fires have been reported to be caused by electrical components. The majority of fire accidents occurred in combiner box, which is presumed to be short-circuit accidents due to dustproof and waterproof failures or heat deterioration of blocking diode. For this reason, the blocking diode installation became optional by revised PV combiner regulation. In this paper, according to the revised regulation, reverse current that generated by voltage mismatch was measured and analyzed in PV array without a blocking diode. The factors that cause voltage mismatch in array are assumed to be shaded PV module and short circuit failure of bypass diode. As the result of experiment, there is no reverse current to flow under shading condition in module, but reverse current flows on the failure of bypass diode in module. According to the module's I-V characteristic curve analysis, open voltage was slightly reduced due to operation of bypass diode in shading. However, it showed that open circuit voltage has decreased significantly in the failure of bypass diode. This indicates that the difference in open voltage reduction of voltage mismatch factor causes reverse current to flow.